Ratio Decidendi Pengadilan Agama terhadap Permohonan Izin Poligami: (Studi Putusan Pengadilan Agama Sidoarjo Nomor 1671/PDT.G/2022/PA.SDA) - Pramesti Ratu Fiqih (CV Rewang Rencang, 2025)
Requests for polygamy permits on the grounds of biological needs have caused debate in religious court practice. This research examines the ratio decidendi of the judge in Decision Number 1671/Pdt.G/2022/PA.Sda which rejected the application. The method used is normative legal research with a statutory approach and a case approach. The results indicated that the judge interpreted the reasons for polygamy strictly and did not include biological needs as a valid reason according to the law. This research suggests the need for technical guidelines from the Supreme Court so that legal interpretation is more consistent and does not harm women's rights.